PEMODELAN WAKTU TUNGGU PENUMPANG PADA JALUR ANGKUTAN DALAM KOTA PALU MENGGUNAKAN ALJABAR MAX-PLUS - Natalia, Y; Sudarsana, I W; Lusiyanti, D (Program Studi Matematika, Universitas Tadulako, 2019)
Passenger waiting time is the time required by passengers starting from the stops until getting transport. The purpose of this research is to get the model of waiting time passengers on the freight line in the Palu city. The first step is the preparation of directed graphs based on the existring routes, then calculate the mileage and travel time using synchronization rules and power algorithm with initial vector ð‘¥ = 0 obtained the value ð‘ = 2, ð‘ž = 1 and ð‘ = 102by using the appplication rock Scilab 5.5.2 and Map-Plus Toolbox obtained eigenvalues as the departure period of 102 and eigenvektor as the initial departure time.Keywords : Eigenvalues, Eigenvectors, Max-Plus Algebra, Waiting Time.